2015
DOI: 10.1111/hex.12435
|View full text |Cite
|
Sign up to set email alerts
|

Defining continuity of care from the perspectives of mental health service users and professionals: an exploratory, comparative study

Abstract: BackgroundContinuity of care (COC) is central to the organization and delivery of mental health services. Traditional definitions have excluded service users, and this lack of involvement has been linked to poor conceptual clarity surrounding the term. Consequently, very little is known about the differences and similarities in the conceptualization of COC by mental health service users and professionals.ObjectiveTo explore and compare mental health service users’ and professionals’ definitions of COC.MethodsU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 34 publications
(95 reference statements)
2
56
0
1
Order By: Relevance
“…The DC users reported larger social networks, but did not experience better quality in their relationships than non-users with psychiatric disabilities (Argentzell, Leufstadius, & Eklund, 2013). Furthermore, the results of a British study showed that DCs met an important need for social contacts and enhanced continuity of the users' social context (Sweeney et al, 2016).…”
Section: Social Network Among Users Of Clubhouses and Day Centresmentioning
confidence: 99%
“…The DC users reported larger social networks, but did not experience better quality in their relationships than non-users with psychiatric disabilities (Argentzell, Leufstadius, & Eklund, 2013). Furthermore, the results of a British study showed that DCs met an important need for social contacts and enhanced continuity of the users' social context (Sweeney et al, 2016).…”
Section: Social Network Among Users Of Clubhouses and Day Centresmentioning
confidence: 99%
“…Alongside the overarching dimension of experienced continuity, the two dimensions of cross‐boundary and longitudinal CoC may be considered to be key anchors of care continuity (Ware et al., ). Cross‐boundary continuity is defined as effective coordination of care between professionals and services involving good management of links between services, professionals and components of care (Adair et al., ; Sweeney et al., ; Uijen et al., ; Ware et al., ). Longitudinal continuity is defined as having care delivered by as few professionals as possible with minimal gaps in treatment (Burns et al., ; Ware et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The concept of ‘contextual continuity,’ defined as care which is sustained within a person's preferred social relationships in the community, is identified as a component of CoC in a number of studies in this review (see Table ; n = 5). The availability of day centres (Rose et al., ; Sweeney et al., ), supported housing (Burns et al., ; Ware et al., ), and peer support (Sweeney et al., ) are considered to be contributors to contextual continuity. Service users find the option of attending day centres a valuable contributor to their overall care according to two studies (Rose et al., ; Sweeney et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations